Evaluation of cytomegalovirus infection/disease in IgG positive renal transplantation recipients on valaciclovir prophylaxis - Tugba Sari; Belda Dursun; Mevlut Ceri; Cagri Ergin; Huseyin Turgut; Murat Ozban (Journal of Infection in Developing Countries)
Introduction: The reactivation of CMV (Cytomegalovirus) in renal transplant recipients may be manifested across a clinical spectrum from asymptomatic viraemia to organ rejection. The purpose of this study is to evaluate the patients who have experienced CMV infection after renal transplantation in the last twelve years, and to assess the efficacy of valacyclovir.